Towards Sustainable Solutions to South Africa’s Energy Crisis: Lessons from South Korea for the Gas-to-Power Programme - Mkhize, Nkosingiphile; Nel-Sanders, Danielle (International Journal of Energy Economics and Policy, 2024)
This article discusses the Gas-to-Power programme in Korea as a case study for South Africa’s attempts to develop Gas-to-Power alternative energy technology. A programme that the government believes could address the nation’s present energy crisis. South Africa’s government has made the development of clean and alternative energy sources a high priority in order to overcome the current energy crisis. This is due to the tremendous increase in global energy use, especially in emerging nations. This essay utilises a qualitative research methodology and secondary data as a result. The report stated that South Africa must take the following steps to bolster its efforts: implementing executable rules and regulations and developing a clear and legitimate demand for the LNG2P energy technology.